Marawi a city of the living past - Eslao, Rufino O. (Education quarterly.)
"Data for this chapter were taken from the Census Report of 1960, data furnished by three Maranao students of the University of the Philippines, and the personal observations of the writer when he was assigned at the Mindanao State University, Marawi City, from 1964-1966."